Manajemen Peningkatan Kepercayaan Diri Siswa Melalui Layanan Bimbingan Kelompok di Kelas X SMAN 1 Parigi - Aidah Fitri Robi'ah Aziz; Nada Nurfadilah; Elsa Istiqomah; Hilman Farid; Dede Nurul Qomariah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
This study aims to explore the management of confidence-building in students through group guidance services in the 10th grade at SMAN 1 Parigi. The study employs a descriptive method with a qualitative approach, involving data collection techniques such as observation, in-depth interviews, documentation studies, and data source triangulation. The research process includes planning, organizing, implementing, and controlling group guidance services focused on enhancing students' confidence. The results show that group guidance services are effective in boosting students' confidence through active participation in group discussions, role-playing, and other activities designed to motivate students to express their opinions and feelings. The school counselors play a crucial role in facilitating and directing the group guidance sessions and conducting regular evaluations to ensure the program's goals are met. Challenges include students who tend to be reserved and the lack of collaboration between homeroom teachers and school counselors. However, with a closer approach and higher intensity of guidance, it is expected to build closer relationships and trust between school counselors and students, significantly increasing students' confidence.